Upaya Padang TV Dalam Meningkatkan Pemirsa Program Acara Sumbar Rancak Bana - Fajri, Fauzan; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In the context of broadcast media in Indonesia, especially television broadcasters such as Padang TV, there are complex challenges and opportunities. However, data shows that television media still plays an important role in people's lives, with high viewing rates. However, the shift in consumption patterns towards internet-based services is a challenge that television stations must face. The phenomenon of viewers moving to cable TV and internet services has resulted in a decline in interest in local broadcasts. This research discusses how Padang TV's efforts to increase viewers through the Sumbar Rancak Bana program. The research method used is a qualitative approach, collecting and analyzing data in the form of words and human actions. This research is descriptive, providing a description and analysis of the research results without making broad conclusions. The analysis and theories used reveal that Padang TV's efforts to increase viewers on the Sumbar Rancak Bana program are in accordance with the theory of media convergence by Henry Jenkins. Convergence of Technology, Business and Content is used by Padang TV, where this theory recognizes the two-way interaction of viewers and media and the role of viewers in shaping experiences. Padang TV implements the Marketing Mix in the Rancak Bana program, with diverse content and supporting facilities that sustain the program. The diversity of Padang TV's viewers in demographics, geography and interests is reflected in the different classifications, showing suitability to the program presented.